Cinematic Intermediality Theory and Practice - Schmid, Marion; Knowles, Kim (Edinburgh University Press, 2021)
As a fundamentally hybrid medium, cinema has always been defined by its interactions with other art forms such as painting, sculpture, photography, performance and dance. Taking the in-between nature of the cinematic medium as its starting point, this collection of essays maps out new directions for understanding the richly diverse ways in which artists and filmmakers draw on and reconfigure the other arts in their creative practice. From pre-cinema to the digital era, from avant-garde to world cinema and from the projection room to the gallery space, the contributors critically explore what happens when ideas, forms and feelings migrate from one art form to another. Giving voice to both theorists and moving image practitioners, Cinematic Intermediality: Theory and Practice stimulates fresh thinking about how intermediality, as both a creative method and an interpretative paradigm, can be explored alongside probing questions of what cinema is, has been and can be.